Water induces the same crown shapes as Li+ or Na+ in 15-crown-5 ether: a broadband rotational study. Issue 6 (9th November 2018) - López, Juan C.; Pérez, Cristóbal; Blanco, Susana; Shubert, V. Alvin; Temelso, Berhane; Shields, George C.; Schnell, Melanie
Abstract : Complexation with water reduces the structural landscape of 15-crown-5 ether to the two forms observed for Li + or Na + complexes. Abstract : 15-Crown-5 ether (15C5) and its complexes with water have been studied using broadband Fourier transform microwave spectroscopy in a supersonic jet. A new conformer of 15C5 has been observed and established as the new global minimum out of a total of nine isolated structures. In addition, two 15C5–H2 O and two 15C5–(H2 O)2 clusters have been observed. The cluster structures have been unambiguously identified through the observation of water 18 O isotopologue spectra. In all the clusters, at least one water molecule, located close to the axis of the 15C5 ring, interacts through two simultaneous hydrogen bonds to the endocyclic oxygen atoms. This interaction reshapes the 15C5 ring to reduce its rich conformational landscape to only two open structures, related to those found in complexes with Li + or Na + ions. In the most abundant 15C5–(H2 O)2 form, the two water molecules repeat the same interaction scheme while binding to opposite sides of the ring. In the second most abundant dihydrated form the two water molecules lie on the same side of the ring. This finding is exceptionally rare because water–water interactions typically prevail over the formation of additional solute-water contacts, and it showcases the particular binding features of crown ethers.